What to Teach and How to Teach: Artificial Intelligence Education in Primary and Secondary Schools - Xia, Xuyue (Science Insights Education Frontiers, 2025)
With the growing impact of artificial intelligence (AI) technology on human society, many countries have introduced AI education into their basic education curricula to facilitate their young generation’s adaptation to future societal development. This study is a review of the current state of primary and secondary AI education from the standpoints of “what to teach” and “how to teach” and finds that AI literacy development is the paramount objective despite the differences in AI education purposes among various countries; that current AI curriculum content primarily includes basic AI knowledge and techniques, AI applications, and ethics of AI; and that a wide variety of pedagogical approaches have been adopted in AI education, including lecture, group study, project-based learning, and activity-based learning. The article also summarizes common AI teaching tools in use. Issues with current AI education are discussed as well.